1993
DOI: 10.1093/jee/86.2.494
|View full text |Cite
|
Sign up to set email alerts
|

Relative and Seasonal Abundance of Beneficial Arthropods in Centipede grass as Influenced by Management Practices

Abstract: Pitfall traps were used to monitor the seasonal activity of arthropod preda tors, parasitoids, and decomposers in replicated plots of centipedegrass turf for 3 yr (1989-1991) at two locations. During 1990 and 1991, the influence of single or combined herbicide, insecticide, and fertilizer applications on these beneficials was assessed. In total, 21 species of carabids in 13 genera and 17 species of staphylinids in 14 genera were represented in pitfall-trap collections. Nonsminthurid collembolans, ants, spiders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 12 publications
4
23
0
Order By: Relevance
“…In the present study, significantly higher population of macro arthropods was recorded in the organic farming (2.20 folds increase) over conventional farming is might be due to the abundance of organic matter, microbial biomass, optimum moisture, soil temperature and food availability. The present findings are corroborating with many workers (Abilasha et al, 2013a: Braman and Pandley, 1993: Gkisakis et al, 2014: Doring and Kromp, 2003: Naureen et al, 2010 they conclude that application of insecticides adversely affected the beneficial arthropods like ants (Formicidae), spiders (Araneae) and parasitic hymenoptera and others declining of macro-invertebrates was less pronounced in organically managed fields (low input) as compared to high input farming.…”
Section: Macro Arthropodssupporting
confidence: 92%
“…In the present study, significantly higher population of macro arthropods was recorded in the organic farming (2.20 folds increase) over conventional farming is might be due to the abundance of organic matter, microbial biomass, optimum moisture, soil temperature and food availability. The present findings are corroborating with many workers (Abilasha et al, 2013a: Braman and Pandley, 1993: Gkisakis et al, 2014: Doring and Kromp, 2003: Naureen et al, 2010 they conclude that application of insecticides adversely affected the beneficial arthropods like ants (Formicidae), spiders (Araneae) and parasitic hymenoptera and others declining of macro-invertebrates was less pronounced in organically managed fields (low input) as compared to high input farming.…”
Section: Macro Arthropodssupporting
confidence: 92%
“…and herbicides (atrazine and 2, 4-dichlorophenoxyacetic acid) used for broadleaf weed control. Cockfield and Potter (1984) and Braman and Pendley (1993) reported similar complexes of natural enemies associated with both cool-and warm-season turfgrasses in other regions in the United States, although both found greater diversity of beneficial arthropod species. Because buffalograss has fewer insect pests (prey species) than most other turfgrasses, it was not unexpected to find fewer natural enemies as well.…”
Section: Resultsmentioning
confidence: 94%
“…Total numbers of natural enemies collected from high and low maintenance sites were not significantly different. Several studies (e.g., Potter 1985, Braman andPendley 1993) have shown that both the abundance and species composition of beneficial arthropods in turfgrasses can be influenced by the type and level of management. Our results, however, suggest that natural enemy composition and abundance in buffalograss is not strongly affected by the level of turfgrass maintenance as defined by this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…), and spiders] for up to 40 d (Mack 1992). Braman and Pendley (1993) evaluated the effects of chlorpyrifos (emulsifiable formulation; dose not specifted) on beneficial arthropods inhabiting turf. Collembolans, ants, spiders, and parasitic Hymenoptera showed transient decreases in abundance following chlorpyrifos application.…”
Section: B Terrestrial Field Studiesmentioning
confidence: 99%